A Helping Hand or the Long Arm of the Law? : Experimental Evidence on What Governments Can Do to Formalize Firms - de Adrade, Gustavo Henrique (Published by Oxford University Press on behalf of the World Bank, 2017)
We conducted a field experiment in Belo Horizonte, Brazil to test which government actions work to encourage informal firms to register. We find zero or negative impacts of information and free cost treatments and a significant but small increase in formalization from inspections. The local average treatment effect estimates of the inspection impact are larger, providing a 21 to 27 percentage point increase in the likelihood of formalizing. The results show that most informal firms will not formalize unless forced to do so, suggesting that formality offers little private benefit to these firms.